TMIC-10. TUMOR-ASSOCIATED NEUTROPHILS PROMOTE GLIOBLASTOMA GROWTH VIA OSTEOPONTIN IN A TARGETABLE MANNER. (6th November 2017) - Yagnik, Garima; Nguyen, Alan; Mueller, Soeren; Alvarado, Beatriz; Watchmaker, Payal; Kriegstein, Arnold; Diaz, Aaron; Aghi, Manish K
Abstract: INTRODUCTION: While tumor-associated macrophages have been shown to exert pro-tumoral effects in glioblastoma, there is limited data on the function of tumor-associated neutrophils (TANs), particularly given their role in systemic inflammation. METHODS: To characterize TANs, our lab isolated CD11b+ CD66b+ CD15+ TANs from patient gliomas (n=16) by FACS and performed single cell sequencing and functional assays examining neutrophil recruitment and downstream effects. RESULTS: TANs represented 1.4% (range=0.04-9.7%) of glioma cell suspensions. TANs increased as prognosis worsened: in high- vs. low-grade gliomas (2.2% vs. 0.3%, P=0.09), bevacizumab-resistant vs. naive GBMs (9.7% vs. 0.9%), and wildtype IDH1-R132 vs. mutant H132 variants (2.2% vs. 0.6%). Cultured bevacizumab-resistant and IDH1-R132 cells exhibit increased neutrophil chemotactic attraction (P<0.05) and increased levels of neutrophil chemoattractant leukotriene B4 (P<0.01) compared to bevacizumab-responsive and mutant IDH1-H132. TCGA analysis revealed higher levels of neutrophil marker myeloperoxidase in IDH1 wildtype vs. mutant GBMs (P<5x10 -6 ). Principal component analysis of TAN single cell expression data elucidated novel candidate genes defining anti-tumoral N1 vs. pro-tumoral N2 subtypes: CCL20, SPARCL1, AKT2, FGF1, RAP2B, HMOX1, SPP1, FTL, PDGFD, and PDGFA. Reciprocal qPCRs of these genes in tumor cells and neutrophils cultured in conditioned media (CM) revealed osteopontin (SPP1) as a mediator of TAN-tumor crosstalk and a strong N2 protumoral candidate gene. Circulating neutrophils expressed no detectable SPP1, while TANs showed a three-fold increase in response to tumor cell CM. Tumor cells cultured in neutrophil CM demonstrated increased proliferation, which was eliminated with an osteopontin blocking antibody (P<0.01). CONCLUSIONS: Through reciprocal cross-talk, glioma cells recruit circulating neutrophils into tumors and convert them into a N2 pro-tumoral subtype, which in turn promote glioma cell proliferation and are associated with poor prognosis glioma types. Single cell sequencing identified genes defining potential N1/N2 subtypes, with osteopontin emerging as a potential therapeutic target to inhibit the pro-tumoral effects of TANs.